(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1999)
The paper deals with singularly perturbed differential inclusions with time lag. The limit behaviour of the solution set when the singular parameter tends to zero is investigated. The limits of the fast solutions are considered as Radon probability measures. Then the upper semicontinuity of the solution set with respect to uniform convergence of the slow motions and to weak probability convergence of the fast motions is examined.